Danzig Diele im Artushof. - Voss, Arno. (Danzig : Verlag Arno Voss, 1935)
Przedstawia Sień Gdańską, ok. 1940 r.
Data wg działalności wyd.
Keywords: Karty pocztowe -- Polska -- Gdańsk -- 1900-1945.; Gdańsk (Polska) -- 1900-1945 -- karty pocztowe